The Effect of Process Approach on Students’ Writing Competency at SMK Negeri 1 Kubutambahan Bali - Sukanaya, Gede (Journal of Education Reseach and Evaluation, 2020)
This study is intended to explore the effect of process approach on students’ writing competency at SMK Negeri 1 Kubutambahan Bali. This study was experiment with pretest-posttest design. This study involved 30 students and the experiment was conducted three months. The data were collected through writing test. The data were analyzed using descriptive and inferential analysis.. The result shows that the students’ mean score in pretest was 6.3 and the students’ mean score in posttest was 7.7. The result of t test shows a significant difference between pretest and posttest with Sig. (2-tailed) = 0.000. It is suggested that English teacher should be focusing on the process of writing instead of product especially for English students who are still having low language proficiency. The result of the study implies that writing is a process. Writing is a process. In the process, the role of revision, which includes comments and suggestions are very helpful for students in improving their writing.